INTENSE MIGRATION FROM HARPOOT TO AMERICA WITH NEW DOCUMENTS (1870-1920) - Güher, Ebru; Açıkses, Erdal (My University, 2019)
As in the case from various places of the world, there were people emigrating from Anatolia tothe New World America, once- especially in the early part of twentieth century- described as theland of opportunities, because of the reasons like trading, education, etc. The first immigrantsfrom Harpoot to America were generally the students of the missioners, those sent by themissioners for education. Later on, a considerable amount of Turkish migration occurred fromHarpoot to America particularly because of the activities of missioners and then trading andother expectations. Specially Armenians, among the Non-Muslims migrated to America, took partthere in the centre of a campaign opponent to Turkey and caused this matter to turn out to be apolitical issue in this dimension. A big part of the Muslims migrated to America adhered to theirreligion and motherland, constructed fountains, mosques on behalf of their names and were thefounders of first Turkish associations. The emigrants of Harpoot, discontented with those,donated millions of dollars from the money they earned in America to various charities in Turkey.Besides, they came back to Turkey during the War of Independence to defense their country. Inthis study, migration from America to Elazığ / Harpoot region was evaluated with newdocuments.
Keywords: Tarih; Uluslararası İlişkiler